Variables Influencing Physical Activity for Children With Developmental Disabilities Who Exhibit Problem Behavior - Livingston, Cynthia P.; Schneider, Delaney E.; Melanson, Isaac J.; Martinez, Sarah E.; Anderson, Heather; Bryan, Samantha J. (Behavioral interventions, 2025)
ABSTRACT Physical activity is associated with several health and non‐health‐related benefits for children with and without disabilities. Most children do not meet the Centers for Disease Control and Prevention's recommendation of at least 60 min of moderate‐to‐vigorous physical activity daily. Children with intellectual and developmental disabilities (IDD) are even less likely to meet these standards than their neurotypical peers. Thus, there is a need to identify ways to combat physical inactivity by identifying variables influencing physical activity in this population. The present study assessed the effects of activity contexts (Experiment 1) and social and nonsocial consequences (Experiment 2) on physical activity and problem behavior for children diagnosed with autism spectrum disorder (ASD) who exhibited problem behavior. In both experiments, we identified one or more conditions that effectively increased physical activity relative to a control. Additionally, little to no problem behavior was observed.